Analysis of speed strategies during World Orienteering Championships - Gasser, B. A. (Journal of Human Sport & Exercise, 2018)
The aim of this study was to analyse if better orienteers run more constant yielding to suggest the better the place, the more constant the pace. In principle, this premise is supported from a biological point of view of the aerobe-anaerobic threshold concept, which is well elucidated in long distance running and implies that a constant pace slightly below the threshold leads to maximal performance through regularly use of cardiopulmonary and musculoskeletal system. To test this assumption race times of orienteers from the world championships at the Swedish Westcoast in Strömstad / Tanum were analysed concerning their steadiness of speed during the final course of middle and long distance races. Interestingly statistical analyses mainly support the premise of relevance of steadiness in running. In woman, for long/middle distance a coefficient of determination between time and steadiness (calculated as standard deviation of all percentage deviations of individual split times and best time) of R2 = 0.254 respectively of R2 = 0.825 was detected. In men, for long/middle distance of R2 = 0.176 respectively of R2 = 0.472. Although, the method does not allow to strictly distinguish between cognitive and biological factors, it is implied that world class orienteers or more general orienteers get best results if running as constant as possible probably slightly below anaerobic threshold.